Demand for recycling filament in 3D printing - Takács, Ágnes; Kmetz, Barbara (Design of Machines and Structures, 2020)
In the study the brief history of 3D printing is written, how the recent past and present is changing the open source movement. The FDM extrusion technology is reviewed in the text, also the areas where the technology can be used. There is a detailed description about the Creality Ender 5 printer and its printed objects. The study’s next main part contains the conceptual design of a filament recycling machine. After the needed market and patent research the functions are established, concepts of the machine are determined. These were evaluated and an optimal sketch was chosen as a result